UPAYA PENINGKATAN KETRAMPILAN KADER TENTANG METODE BOM MASSAGE DALAM KEGIATAN PENDAMPINGAN IBU NIFAS DAN KELUARGA DI POSYANDU LESTARI ASIH KADIPIRO BANJARSARI SURAKARTA - Tresia Umarianti; Rahajeng Putriningrum; Aris Prastyoningsih; Budi Prasetyo; Rika Ade Ima; Chusnul Karlina Lulu Damayanti; Chiendy Revina; Niea Darmawanti (Yayasan Education and Social Center, 2021)
Breast milk (ASI) is the best food for babies up to 6 months of age. The success of exclusive breastfeeding nationally is only 33.6%, and 35% according to the WHO Global Data Bank 2012. The smoothness of the lactation process is influenced by breast care, breastfeeding frequency, maternal psychology, maternal health, and contraception. Based on a preliminary study of 12 cadres through whatshapp group interviews, it was found that there were no cadres who knew about the BOM Massage method at all. This method helps the production and expulsion of breast milk through a compilation of Breastcare, Oxytocin and Marmet techniques. Cadres also have not received training on how to increase milk production through skills. In general, to stimulate the production of breast milk, the surrounding community uses certain foods that are culturally or passed down from parents to be consumed. The purpose of Community Service is to increase the knowledge and skills of Cadres about the BOM Massage method to increase breast milk production and relaxation in postpartum mothers. The method used for training is the BOM Massage Method through Offline by giving lectures, simulations and role play. There are 11 cadres who take part in service activities. After the pre and post tests were held, there was an increase in knowledge of 92%. The results of the Roleplay implementation of the BOM Massage method cadres can carry out well according to the SOP and Tools for the implementation of the BOM Massage method